A checklist of marine littoral mites (Acari) associated with mangroves - Chatterjee, Tapas; Pfingstl, Tobias; Pešić, Vladimir (Zootaxa, 2018)
The marine littoral mangrove mite fauna comprises members of the prostigmatid families of Halacaridae and Pontarachnidae, the mesostigmatid family Eutrachytidae, the astigmatid family Hyadesiidae and ten different families of Oribatida. The majority of this fauna is made up by the Halacaridae and Oribatida with 31 species each, the Pontarachnidae, Hyadesiidae and Eutrachytidae represent the minority with nine species altogether. So presently, 71 species are known to occur in mangrove ecosystems, more than half of which are exclusively associated with this habitat. Marine littoral mites have been reported from nearly all large mangrove ecosystems of the world, whereas species numbers clearly correlate with sampling effort. Therefore, the real diversity and distribution of mangrove mites is far from being complete and future investigations may reveal further new taxa being present in this environment that is seriously affected by anthropogenic activities.